THE PROBLEM OF BURIAL ORGANIZATION AND HONORING THE MEMORY OF UNR SOLDIERS IN POLAND IN 1989–2005 (Південний архів (історичні науки), 2021)
After 1989, the change of the political system in Poland from a totalitarian to a democratic one allowed the Ukrainian national minority in Poland to develop its own national life. In addition to cultural and political activities, people became interested in their own history, and the process of reviving their own historical memory began. One of its elements was the problem of honoring the memory of people important to the Ukrainian nation who were buried in what is now Poland. Among the burials were the graves of UPR soldiers who found themselves in Poland and died as a result of the Polish-Bolshevik war of 1920. Under the Polish People’s Republic, their graves were both intentionally and unintentionally abandoned, and the then authorities did not agree to restore them. Such an opportunity arose only after 1989, but even here the Ukrainian community met with resistance from some representatives of central and local authorities. However, several cemeteries and buildings dedicated to UPR soldiers, Poland’s allies in the war with Bolshevik Russia, were tidied up and renovated.
Keywords: Poland, Ukraine, UPR, Ukrainian military cemeteries, commemoration.